Analysis of the Intrinsic Elements of Andrea Hirata's Edensor Novel and Its Relevance to Learning Materials Reviewing Fiction Works for Class VIII SMP Negeri 23 Medan - Purba, Pami Jeciou; Harahap, Muharrina (Universitas Pahlawan Tuanku Tambusai, 2026)
The study of literary works in educational contexts plays an important role in developing students’ analytical and interpretative skills, particularly in understanding intrinsic elements of fiction. However, the selection of appropriate literary texts that align with curriculum demands and students’ characteristics remains a challenge. This research aims to describe the intrinsic elements of the novel Edensor by Andrea Hirata and to analyze its relevance to teaching review texts of fiction for eighth-grade students at SMP Negeri 23 Medan. This study employs a descriptive qualitative method with a structuralism approach, focusing on the analysis of intrinsic elements, including theme, characters and characterization, plot, setting, point of view, language style, and moral message. The primary data source is the novel Edensor, while supporting data were obtained through questionnaires distributed to 63 eighth-grade students. The results show that Edensor contains complete and interconnected intrinsic elements that construct a coherent narrative. The main theme revolves around the struggle to achieve dreams through education, supported by strong character development, a progressive plot, varied settings, first-person point of view, aesthetic language style, and meaningful moral values. Furthermore, the questionnaire results indicate a relevance level of 82.4%, categorized as highly relevant. This suggests that the novel aligns well with the learning objectives of reviewing fiction texts in the Merdeka Curriculum and effectively supports students’ understanding of intrinsic literary elements. In conclusion, Edensor by Andrea Hirata is suitable as an alternative teaching material for learning to review fiction texts in eighth grade, as it meets both theoretical and empirical criteria and aligns with students’ learning needs.